The Effect of Time Management and Teacher Performance on the Formation of Students' Disciplined Character at MAN 2 Bone - Wafirah Khairun Nisaa; St. Azisah; Mardhiah Hasan (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to determine the effect of time management and performance of teachers on the formation of students' disciplinary character at MAN 2 Bone. The focus of the study is detailed into four sub-problems, namely: description of teacher time management, teacher performance, and student disciplinary character; the effect of time management on disciplinary character; the effect of teacher performance on disciplinary character; and the simultaneous effect of both. This study uses a quantitative approach with the ex post facto method. The population is 687 students, with a sample of 87 respondents selected through the Proportionate Stratified Random Sampling technique using the Slovin formula. Data collection techniques are carried out through questionnaires and documentation, and are analyzed descriptively and inferentially. The results of the descriptive analysis show that teacher time management, teacher performance, and student disciplinary character are in the moderate category. Inferentially, there is a significant effect of teacher time management on disciplinary character (t count = 5.331> t table = 1.987), and a significant effect of teacher performance on disciplinary character (t count = 4.740> t table = 1.987). Simultaneously, both also have a significant effect (F count = 15.881 > F table = 3.10; sig = 0.001 < 0.05). The implications of the study indicate that teachers who are able to manage time well and have optimal performance can be role models in shaping student discipline. Therefore, school support is needed through training, monitoring, and strengthening of a culture of discipline. Further research is suggested to examine other factors that also influence the formation of disciplined character.